PEMILIHAN DAN PEMBENTUKAN KATA DALAM BERITA MEDIA CETAK DI KALIMANTAN SELATAN - NFN Musdalipah (Kantor Bahasa Provinsi Gorontalo, 2020)
Journalists have a strong ability to influence society through the language which they use in conveying information. However, some of the journalists do not have proficiency in standard language. Hence, there is a need to study the word choice and formation in printed mass media, published particularly in South Kalimantan. The study is intended for the journalists to use as a reference to improve their proficiency in using language in mass media. Qualitative descriptive analysis is used to describe the data. The data sample consists of 29 news articles from five printed mass media: Radar Banjar, Banjarmasin Post, Kalimantan Post, Mata Banua, and Barito Post. The selected article was published in March 2019. The result showed word choice and word formation errors consist of errors in using conjunctions that link words in a sentence and between sentences, prepositions, loan words, substandard words, and derivatives.